Des codices dans les archives. Ranger et coter la documentation administrative et réglementaire d’une collégiale : le cas de Saint-Just à la fin du xve et au début du xvie siècle - Jean-Benoît Krumenacker (Bulletin du Centre d’Études Médiévales d’Auxerre)
This article highlights the evolution of a set of administrative codices of the collegiate church of Saint-Just, arranged within the charter and the many titles of the chapter. This study is based mainly on an inventory of the collegiate church from 1486 and its various additions, which show about fifteen papers of the collegiate church between the titles of the church’s obediences. We can see an old deposit to which various documents, including chapter acts, were added during the first half of the 15th century. They even end up becoming the only type of document archived at this location. The documentation also shows how to name and store these volumes. An alphabetical listing was introduced but quickly disappeared in favour of a denomination according to the name of the secretary. However, these fluctuations show an interest in these documents, which can be seen in their preservation to this day.